PATOLOGI BIROKASI DALAM PELAYANAN PUBLIK (STUDI PELAYANAN PEMBUATAN E-KTP DI UNIT PELAKSANA TEKNIS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KECAMATAN TAPUNG TAHUN 2016) - M. Indra Tristianto; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The main obstacle in the implementation of good public services in Indonesia is the bureaucratic pathology that is still felt by the community for the treatment received from government officials. To overcome the bureaucratic pathology, policies are needed that must be carried out consistently by each apparatus and society together. This research is about the forms of existing bureaucratic pathology and government efforts to overcome the bureaucratic pathology. This research was conducted with the aim to find out the forms of bureaucratic pathology and efforts to overcome the bureaucratic pathology in making E-KTP which was carried out in the Tapung District Technical Implementation Unit (UPTD) in 2016. The main problem in this research is that there is still maladministration such as illegal charges made by the E-KTP maker and the low responsiveness of the E-KTP maker in providing services to the community. The theory used in this study is bureaucratic pathology.Based on the explanation above, it can be concluded that; first, the service for making E-KTP in the Population and Civil Registration UPTD in Tapung Sub-district is still not running optimally because there are still a number of officers who carry out illegal levies. In addition there is still discrimination in service or differences in services provided by the officers to the community and the responsiveness or skills of officers who are still low. Secondly, the efforts made to overcome the bureaucratic pathology that occurred in the Population and Civil Registration UPTD in Tapung Subdistrict were carried out in a structured manner, namely a friendly culture in government-oriented services as a provider to the needs of the community as users need to be further enhanced and important in influencing the level of satisfaction of the community where the service is equitable and without discriminating status and position which is supported by the availability of adequate facilities and infrastructure in the service of population administration, in a fast and appropriate service in accordance with a predetermined time.Keywords: Bureaucratic Pathology, Bureaucracy, Service